Modeling and simulation of customer dissatisfaction in waiting lines and its effects. (February 2017) - Alvarado-Valencia, Jorge A; Tueti Silva, Gabriela C; Montoya-Torres, Jairo R
A combination of discrete-event and agent-based simulation analysis using a field-tested psychological model for evaluating the effects of customer dissatisfaction in waiting lines beyond balking and reneging was developed. The proposed model assessed the effects that different psychological parameter values and business decisions in waiting lines have on the evaluation of waiting and, therefore, in customer satisfaction and mid-term profit. This model hence becomes a decision-support tool for businesses wanting to model their costs of customer dissatisfaction due to waiting lines in repetitive and competitive environments.